Clinical profile of young females with systemic lupus erythematosus: an observational study - Tandi, Rishman; Kumar, Tanvi; Singh, Atamjeet; Kathura, Harmanpal (International Journal of Advances in Medicine, 2021)
Background: Systemic lupus erythematosus (SLE) is an autoimmune disorder predominantly affecting women of child bearing age group and is known to require significant lifestyle modifications. The manifestations of SLE are myriad and it may virtually affect every system of affected individual. We Undertook this study to know the clinical profile of young female patients having SLE. The aim of the study was to study clinical features and medical therapy of young female patients having SLE. Methods: This was a prospective study in which 60 female patients diagnosed to be having lupus were included on the basis of a predefined inclusion and exclusion criteria. Investigations relevant to the diagnosis such as Antinuclear antibodies, Antiphospholipid Antibodies, Anti B2GP1 IgG, Anti-dsDNA antibody, Anti Smith Antibody and complement (C3 and C4) levels were done in all the cases. Other investigations such as imaging studies were done in selected cases. Clinical features and medical management being taken by these patients were analyzed. SSPS 21.0 software was used for statistical purpose. Results: The mean duration of the disease in studied cases was found to be 6.96±4.51 years. Malar rash was the commonest type of rash seen in these patients and was present in 53 (88.33%). Arthralgia with or without arthritis was seen in 54 (90%) of the cases. Anemia was the most common hematological abnormality and was seen in 17 (28.33%) patients. Renal involvement in the form of proteinuria was seen in 25 (41.67%) cases. The most common form of pulmonary involvement was pleural effusion which was seen in 4 (6.67%) patients. Cardiovascular manifestations were seen in 11 patients (18.33%). Conclusions: SLE usually affect women of child bearing age group and have a myriad clinical presentation. A thorough knowledge of various clinical presentations and a high index of suspicion is necessary to diagnose SLE particularly in its early stages.